GII.P16-GII.2 Recombinant Norovirus VLPs Polarize Macrophages Into the M1 Phenotype for Th1 Immune Responses - Han, Ji Cheng; Li, Qiu Xuan; Fang, Jin Bo; Zhang, Jin Yong; Li, Yi Quan; Li, Shan Zhi; Cheng, Cheng; Xie, Chang Zhan; Nan, Fu Long; Zhang, He; Li, Zhuo Xin; Jin, Ning Yi; et al. (Frontiers in Immunology, 2021)
Norovirus (NoV) is a zoonotic virus that causes diarrhea in humans and animals. Outbreaks in nosocomial settings occur annually worldwide, endangering public health and causing serious social and economic burdens. The latter quarter of 2016 witnessed the emergence of the GII.P16-GII.2 recombinant norovirus throughout Asia. This genotype exhibits strong infectivity and replication characteristics, proposing its potential to initiate a pandemic. There is no vaccine against GII.P16-GII.2 recombinant norovirus, so it is necessary to design a preventive vaccine. In this study, GII.P16-GII.2 type norovirus virus-like particles (VLPs) were constructed using the baculovirus expression system and used to conduct immunizations in mice. After immunization of mice, mice were induced to produce memory T cells and specific antibodies, indicating that the VLPs induced specific cellular and humoral immune responses. Further experiments were then initiated to understand the underlying mechanisms involved in antigen presentation. Towards this, we established co-cultures between dendritic cells (DCs) or macrophages (Mø) and naïve CD4+T cells and simulated the antigen presentation process by incubation with VLPs. Thereafter, we detected changes in cell surface molecules, cytokines and related proteins. The results indicated that VLPs effectively promoted the phenotypic maturation of Mø but not DCs, as indicated by significant changes in the expression of MHC-II, costimulatory factors and related cytokines in Mø. Moreover, we found VLPs caused Mø to polarize to the M1 type and release inflammatory cytokines, thereby inducing naïve CD4+ T cells to perform Th1 immune responses. Therefore, this study reveals the mechanism of antigen presentation involving GII.P16-GII.2 recombinant norovirus VLPs, providing a theoretical basis for both understanding responses to norovirus infection as well as opportunities for vaccine development.